Fatigue life estimation in a hydrogenerator rotor with cracks using the finite element method - Putini, Ednei Pedro Gomes [UNESP]; Silva, Fernando de Azevedo [UNESP] (Springer Nature, 2018)
Fatigue is a mechanical engineering field which has been well studied in recent years. This phenomenon is responsible for causing the great majority of mechanical failures in machine elements. Fatigue analysis in a complex piece with the purpose of determining its durability becomes very complicated when it is performed by means of analytical calculations without the aid of software. Thus, the finite element method, which is studied in several areas and is constantly growing, is the ideal tool for the verification of possible failures due to fatigue in heterogeneous components. This paper offers a numerical simulation by finite element method using the software ANSYS of a hydrogenerator rotor which has presented some cracks. As the manifestation of such defect in hydroelectric plant rotors is not common, it requires a detailed study. The results obtained from this study showed that the cracks in the hydrogenerator rotor have arisen due to fatigue. It has been demonstrated that the method employed is very accurate when it is used correctly and that it provides results which represent reality. Moreover, improved solutions were suggested in order to enlarge the fatigue life of hydrogenerator rotor.
Keywords: Analysis; Cracks; Fatigue; Finite element method; Hydrogenerator rotor